Differences in Kidney Function and Incident Hypertension: The Multi-Ethnic Study of Atherosclerosis - Kestenbaum, Bryan (2008)
BACKGROUND: Kidney disease and hypertension commonly coexist, yet the direction of their association is still debated. OBJECTIVE: To evaluate whether early kidney dysfunction, measured by serum cystatin C levels and urinary albumin excretion, predates hypertension in adults without clinically recognized kidney or cardiovascular disease. DESIGN: Observational cohort study using data from 2000 to 2005. SETTING: The MESA (Multi-Ethnic Study of Atherosclerosis), a community-based study of subclinical cardiovascular disease in adults age 45 to 84 years. PARTICIPANTS: 2767 MESA participants without prevalent hypertension, cardiovascular disease, or clinically recognized kidney disease (an estimated glomerular filtration rate <60 mL/min per 1.73 m(2) or microalbuminuria). MEASUREMENTS: Cystatin C was measured by using a nephelometer, and urinary albumin and creatinine were measured from a spot morning collection. The primary outcome was incident hypertension, defined as systolic blood pressure of at least 140 mm Hg, diastolic blood pressure of at least 90 mm Hg, or use of an antihypertensive medication. RESULTS: During a median follow-up of 3.1 years, 19.7% of the cohort (545 participants) developed hypertension. After adjustment for established hypertension risk factors, each 15-nmol/L increase in cystatin C was associated with a statistically significant 15% greater incidence of hypertension (P = 0.017). The highest sex-specific quartile of urinary albumin–creatinine ratio was associated with a statistically insignificant 16% greater incidence of hypertension (P = 0.192) compared with the lowest quartile. No statistical evidence suggested a multiplicative interaction. LIMITATIONS: Unmeasured characteristics may have confounded observed associations of kidney markers with hypertension. Follow-up was relatively short. Hypertension that may have occurred between study visits or hypertension that was not captured by standard cuff measurements may have been missed. CONCLUSION: Differences in kidney function, indicated by cystatin C levels, are associated with incident hypertension among individuals without clinical kidney or cardiovascular disease. These population-based findings complement experimental work implicating early kidney damage in the pathogenesis of essential hypertension.